Evaluation of the Relationship between Sella Turcica Bridging and Dental Anomalies - Karaman, Ahmet; cigerim, saadet cinarsoy, Assistant Professor; Kechagia, Nourtzan, Research Assistant (UI Scholars Hub, 2021)
Objectives: This study aims to evaluate the relationship between the morphological variations of Sella Turcica (ST) and dental anomalies. Methods: This study included 765 individuals between the ages of 13 and 35. ST morphology was examined in 3 groups as no calcification, partially calcified and completely calcified according to the interclinoid ligament (ICL) on lateral cephalometric films, and it was examined and evaluated in terms of its relationship to impacted canines (unilateral and bilateral), impacted teeth (except 3rd molars), root dilaceration, tooth deficiency (upper incisor lateral - lower and upper second premolar), supernumerary tooth and taurodontism. Results: The rates of supernumerary teeth, lateral and premolar tooth deficiency and root dilaceration in total calcification of ICL were significantly higher than those in ICL with no calcification. The rates of taurodontism, unilateral and bilateral impacted canine teeth and impacted teeth in ICL with no calcification were found to be significantly lower than those in the partial and total calcification of ICL. Conclusion: In this study, a statistically significant relationship was found between ST morphology and dental anomalies. Examination of sella turcica bridging (STB) variations in a large population will be guiding for the early detection of dental anomalies.